Pemberdayaan Masyarakat Melalui Budi Daya Ikan Pada Kelompok Mina Sejahtera di Dusun Patokbeusi, Subang - Pramono Adi, Catur; Suhermanto (indonesia), Achmad; Prabowo (indonesia) et al, DH. Guntur (Fakultas Pertanian_Universitas Tidar, 2025)
Community empowerment is a strategic effort to improve people’s welfare through capacity development and skill enhancement. This program was carried out in Patokbeusi Hamlet, Subang Regency, West Java, focusing on catfish farming as a practical and accessible livelihood alternative. Implemented by the Department of Aquaculture at the Karawang Polytechnic of Marine and Fisheries, the program involved training and mentoring activities for the local community, specifically the Mina Sejahtera group. The empowerment activities included technical training in fish pond construction, fish feeding, disease control, and marketing strategies. A total of 15 participants joined the program. The catfish farming was conducted using simple pond systems with tarpaulin-lined structures, making it feasible for communities with limited capital. During the mentoring phase, 6,000 catfish were cultivated across three ponds and yielded approximately 1,000 kg of harvest. The program not only increased the knowledge and technical skills of the community members but also contributed to their entrepreneurial capacity. Evaluation results indicated a significant improvement in participants’ understanding and implementation of aquaculture practices. Moreover, the formation of formal fish farming groups (Pokdakan) enhanced their access to markets and strengthened community organization. The success of this initiative demonstrates that integrated and participatory empowerment models, when supported by technical guidance and government collaboration, can lead to sustainable socio-economic development. This model can be replicated in other rural communities to tackle unemployment, food insecurity, and low income through accessible aquaculture-based entrepreneurship.